1984
DOI: 10.1063/1.94789
|View full text |Cite
|
Sign up to set email alerts
|

Electric field induced morphological changes in nylon 11

Abstract: Electric field induced changes in the x-ray diffraction pattern of nylon 11 films containing a mixture of the alpha and gamma crystal phases are presented. These changes indicate an orientation of crystallites such that dipoles are aligned in the direction of the poling field. Correlation between this crystal orientation and piezoelectric activity was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…The first significant piezoelectricity in polyamides, odd nylon 11, was reported by Newman et al in 1980 . Since then piezoelectricity and ferroelectricity of odd nylons have been widely investigated . The piezoelectric strain coefficient d 31 is as high as 3 pC/N for poled polyamide 11 films at room temperature .…”
Section: Introductionmentioning
confidence: 98%
“…The first significant piezoelectricity in polyamides, odd nylon 11, was reported by Newman et al in 1980 . Since then piezoelectricity and ferroelectricity of odd nylons have been widely investigated . The piezoelectric strain coefficient d 31 is as high as 3 pC/N for poled polyamide 11 films at room temperature .…”
Section: Introductionmentioning
confidence: 98%
“…Consider a chain subject to a harmonic potential 1 2 k R 2 activated at time tϭ0. In the continuum formalism, the dynamical equations for the monomer locations R(t,n) take the form ͑here T denotes k B ϫtemperature͒ ‫ץ‬R ‫ץ‬t…”
Section: Zimm Model Under a Weak Harmonic Potentialmentioning
confidence: 99%
“…Some synthetic polymers, such as Nylon-11 and poly͑vinylidene fluo-ride͒, exhibit strong responses to an applied electric field and marked piezoelectric properties. 1,2 As for other electroactive polymers, piezoelectric polymers produce appreciable strains under electric fields, and are important materials for actuators and artificial muscles. 2 Recently, Mansky et al have shown that the applied field tends to deform polymer thin films, and results in the alteration of neutron scattering profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The melt pressed film exhibited two strong reflections (100) and (110, 010) at the diffraction angles of 2 θ = 20.32 and 23.17  , which correspond to the  crystalline phase of Nylon11. Solution cast films showed characteristic reflections of 21.6 and23.03 ° indicating the coexistence of gamma and alpha crystalline forms, respectively[44].The electrospun mats showed a broad reflection at 21.6 o , which indicates weakly, ordered hexagonal gamma crystalline form of Nylon11[45].This metastable structure is likely formed because of the influence of two simultaneous events during electrospinning namely, rapid evaporation of solvent and elongation of the solidifying fibers.…”
mentioning
confidence: 99%